Structural, impedance, and modulus spectroscopic studies on Y2/3Cu3Ti3.95In0.05O12 polycrystalline material prepared by flame synthesis method. Issue 7 (8th August 2016) - Singh, Laxman; Yadava, Shiv Sunder; Woo, Won Seok; Rai, Uma Shanker; Mandal, K. D.; Sin, Byung Cheol; Lee, Youngil
ABSTRACT: The polycrystalline material Y2/3 Cu3 Ti3.95 In0.05 O12 (YCTInO) having giant dielectric constant was prepared by the flame synthesis method using metal nitrate and solid TiO2 in ethylene glycol mono-methyl ether. X-ray powder diffraction (XRD) study on the material sintered at 1, 050°C for 15 h reveals the single phase cubic perovskite structure. In Fourier transform infrared (FT-IR) spectroscopy, absorption bands were observed at 583 and 521 cm −1 corresponding to vibrations of Cu–O and 441 cm −1 of Ti–O–Ti, which are confirmed the single phase formation. X-ray photoelectron spectroscopy (XPS) data of YCTInO reveal the presence of Y 3d, Cu 2p, Ti 2p, In 3d, and O1s peaks of the elements, which justify the energy dispersive X-ray spectroscopy (EDX) results and compositional purity of the materials synthesized by the flame synthesis. The dielectric property of this material was studied in the frequency range of 0.01–100 kHz and the temperature range from 298 to 440 K. The electrical behavior of the ceramic studied by impedance and modulus spectroscopy reveal that the dielectric permittivity (ϵr ) values of the YCTInO were dominantly affected by the electrical properties of grain-boundary.